Numerical Study of Mixed Convection in a Channel Filled with a Porous Medium - Ozgen, Filiz; Varol, Yasin (Mdpi, 2019)
The heat transfer of mixed convection in a horizontal channel filled with a porous medium has been studied in this article, given that it plays an extensive role in various technical applications, such as flow of fluid in geothermal resources, formations in chemical industries, the storage of radioactive nuclear waste material, and cooling. Those equations written in a dimensionless form have been solved using the finite difference method for different values of the parameters. The results obtained from the study have been presented through streamlines, isotherms, and both local and average Nusselt numbers. It has been observed that parameters such as the Rayleigh and Peclet numbers have an effect on flow and temperature fields.
Keywords: Mixed heat transfer; channel; porous medium